The role of thalidomide as maintenance after autologous stem cell transplantation in multiple myeloma - Maiolino,Angelo (2009)
Major progress was obtained over the last ten years in the treatment of multiple myeloma (MM). High dose chemotherapy with autologous stem cell transplantation (ASCT) and new drugs such as thalidomide, lenalidomide and bortezomib have completely changed the scenario of MM treatment. ASCT has become the mainstay of MM treatment for patients up to 65 years old. This strategy has been tested in randomized clinical trials which proved that ASCT can improve overall survival of MM patients. Unfortunately, the great majority of these patients will relapse in a few years after ASCT. Strategies of maintenance have been developed trying to improve the results of ASCT. Thalidomide has been tested in this setting in at least 4 randomized clinical trials with a significant impact on response rate, and event free and overall survival.l.